VALUASI EKONOMI JASA HIDROLOGIS TAMAN HUTAN RAYA NIPA-NIPA - Anita Indriasary; La Baco S. (Universitas Haluoleo, 2017)
The economic value of hydrological services produced by Forest Park Nipa-nipa not yet widely known, so the appreciation of forest conservation Forest Park Nipa-nipa still low and the pressure on forest conservation is still ongoing. This study aimed to analyze the regional hydrological services Tahura Nipa-nipa utilized by the community, analyze the value of the economic benefits of hydrological services Tahura region Nipa-nipa and analyze the factors that affect the value of the economic benefits of hydrological services Tahura Nipa-nipa. This research was conducted in two District of the District of West Kendari (Kemaraya Village and Village Punggaloba) and the District of Kendari (Village Mount teak and Kampung Salo). Selection of the location determined by purposive sampling with the consideration that the area of Nipa-nipa Tahura located in District are some community members actively manage water. Sample respondents or informants for the location overall is 60 respondents were randomly chosen. The method used is the procurement cost approach and willingness to pay (Willingness To Pay), which reflects the minimum value of the economic benefits felt by masyarakay who were around the area Tahura Nipa-Nipa which directly utilize water from springs located on the Tahura region. The analysis used is descriptive analysis, analysis of WTP approach and linear regression analysis of two factors.The results showed that the average value of willingness to pay each family (KK) for 60 respondents in two (2) sub-district as spring water conservation efforts in the region Tahura Nipa-nipa and the total value of WTP (Willingness To Pay) is Rp. 42.634 million / year and the potential value of water in the hydrological services utilization Tahura Region Nipa-nipa is Rp. 45.978 million / m3 / year. Results of calculation of economic value of hydrological services produced as a function of the existence of Nipa-nipa Tahura region is only a fraction of the total economic value of water contained within the Nipa-nipa Tahura because there are many other water users who are greater in line with their needs. Keywords: economic value, hydrological services, Tahura Region Nipa-Nipa